Upaya Meningkatkan Perkembangan Sosial Emosional Anak Usia Dini - Nur Hasana Alvi Syahrin; Khodijah; Nurul Hadidah Alhadid; Septia Putri Anggraini; Ziha Fida Utami Tanjung (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research aims to find out how efforts to improve the social emotional development of early childhood, the research approach uses Literature Review study is one type of qualitative research method in which research is carried out in the library through the collection of books, documents, archives, and other types. The results of this study show that efforts to improve early childhood social emotional development have a significant positive impact on their lives. Through such intervention programs, children can develop the skills necessary for success in school, daily life and society as a whole. Collaboration between schools, communities and parents plays an important role in improving early childhood social-emotional development.